Galeri Kopi Lokal Sumatera Dengan Pendekatan Lighting - Joko Priadi; Mira Dharma Susilawaty; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Coffee Gallery is a place that provides educational, information, commercial, which aims to introduce local products of Sumatera, especially in Pekanbaru. The role of public facilities must necessarily have their own comfort and distinctive features. Therefore, the facilities provided are not only exhibition objects but visitors can see directly the process of processing coffee beans to become ready-to-prepare powder. In terms of gallery facilities also provide a place to relax while enjoying various types of processed coffee. Using the lighting approach, the view of the building can express the character of the coffee itself so that in any room can clearly difference and trademark. Through the basic concept of caffeine, the architectural model comes from the results of the transformation of the compound bonding model which becomes the basic form. The nature and character of each coffee is applied to the color and lighting display.Keyword: gallery, coffee, sumatera, pekanbaru, public facilities, lighting, caffeine